PENGARUH SERVICE QUALITY, PRICE, DAN RESTAURANT ENVIRONMENT TERHADAP CUSTOMER LOYALTY MELALUI CUSTOMER SATISFACTION DI RESTORAN JAKARTA - CHANDRA, YIUTO; PRASASTYO, KLEMENS WEDANAJI (E-Jurnal Manajemen Trisakti School of Management (TSM), 2024)
This research aims to determine the influence of service quality, price and restaurant environment variables on customer loyalty through customer satisfaction variables. The object of this research is the Chinese restaurant "Din Tai Fung" in DKI Jakarta. Sample identification was carried out using a purposive sampling method by determining nine sampling criteria, so that a total of 274 respondents were obtained with 257 data respondents who met the criteria and could be used as research samples. This research uses a multivariate analysis model to test the influence of each variable. The research results show that the variables of service quality, price and restaurant environment influence variations in customer loyalty through variations in customer satisfaction.